Setting of import tolerances for fludioxonil in sugar beet roots and bananas. (10th November 2021) - ,; Bellisai, Giulia; Bernasconi, Giovanni; Brancato, Alba; Carrasco Cabrera, Luis; Ferreira, Lucien; Giner, German; Greco, Luna; Jarrah, Samira; Kazocina, Aija; Leuschner, Renata; Magrans, Jose Oriol; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Syngenta Crop Protection AG submitted a request to the competent national authority in France to set import tolerances for the active substance fludioxonil in sugar beet roots and bananas. The data submitted in support of the request were found to be sufficient to derive maximum residue level (MRL) proposals for sugar beet roots and bananas. Adequate analytical methods for enforcement are available to control the residues of fludioxonil in the commodities under consideration at the validated limit of quantification (LOQ) of 0.01 mg/kg and in animal matrices at the validated LOQ of 0.01 mg/kg in milk and muscle and 0.05 mg/kg in liver, kidney, fat tissues and eggs. Based on the risk assessment results, EFSA concluded that the long‐term intake of residues resulting from the use of fludioxonil according to the reported agricultural practices is unlikely to present a risk to consumer health.